(untitled) (Journal of Science and Technology, 2016)
The study sought to evaluate primarily reader services of the U.S.T Library. This was to assess its perfomance as regards the functions expected of a University Library that supports learning/ study, teaching and research, or to see how effectively the reader services unit of the Library has been rendering such services.